"Environment, agriculture and community in Himachal Pradesh" - Richa (Mumbai, 2008)
Various researchers have concentrated on the ethnic and cultural diversity of the Himalayas which has been studied from the classical anthropological viewpoint. Much less is documented however of these societies rich knowledge of the fragile environment and of their strategies for the management of natural resources at the local levels.
Keywords: India--Himachal Pradesh